Outpatient visit modality and parallel patient satisfaction: A multi-site cohort analysis of telemedicine and in-person visits during the COVID-19 pandemic - Nicole Ploog; Jordan Coffey; Laura Wilshusen; bart demaerschalk (The Beryl Institute, 2022)
Telemedicine approaches provide many benefits to patients across both primary and specialty care. Patient acceptance is imperative to successful telemedicine implementation. As telemedicine utilization continues to surge, it is imperative that healthcare organizations have a method for evaluating the patient experience with these types of visits. Previous studies on experience with telemedicine have focused on smaller patient populations with narrow inclusion criteria and limited geographical reach. This research described how patients' satisfaction with video telemedicine-based visits varied based on patient characteristics and how they compare with in-person visits. We obtained and analyzed results from standardized patient experience surveys to compare telemedicine and in-person clinic visits during the COVID-19 pandemic (between July 1, 2020, and June 30, 2021) across a diverse patient population. During the study timeframe, surveys were sent to 1,521,398 patients with a response rate of 20% (307,185). Our organization's unique structure, size, and geographic spread allowed for a deeper and more comprehensive examination of telemedicine participants. Though a few trends emerged in the results, there were no significant differences in patient ratings of telemedicine visits and in-person clinic visits during the same period (p=0.672). This study demonstrated that patient satisfaction with telemedicine visits was non-inferior to in-person outpatient visits during the study timeframe. Experience Framework This article is associated with the Innovation & Technology lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Innovation%20%26%20Technology%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens